Dos ecos do ECA à psicanálise: entre a lógica do bem-estar e a ética do bem dizer - Borges, Michele Donizete Ferreira (2021)
The present study was developed from the questioning about psychoanalitical listening to children and adolescents under the States’s residential care and its relationship with the guarantee of rights. Starting from the question of how to extract the Ethics of Well Said, that is, listening to the subject of desire, from the Logic of Well Fare - present in Social Assistance. To this end, it was important to look back in order to listen today, through a brief historical trajectory of the placement of children and adolescents under State’s care in Brazil, since the colonial period until the approval of the ECA and the developments to the present day, pointing out that the way in which this service was built and as children and adolescents, throughout history, were taken as an object by the Church, Charities and later by the State. For psychoanalysis, listening is always referred to listening the subject of desire regardless of age, so it is necessary to present the concept of child and its constitution as an advent of modernity, as well as the notions of subject and childhood for psychoanalysis. In the third chapter is presented the process of entering a Social Assistance Institution and joining the work team, as it is the necessary condition for the psychoanalyst to operate. The fourth chapter develops some problems of the different apparatus that make up the social assistance network and which are the contributions the psychoanalyst can offer in this field, guided by the ethics of psychoanalysis, precisely the Ethics of Well Saying the Desire. Lastly, the Greek Tragedy Antigone is presented, of which Lacan used to think the ethics of psychoanalysis, and it is articulated with fragments of a case attended at the Institution. Finally, some important questions were presented about the consequences - still very uncertain - of the new coronavirus (COVID-19) in guaranteeing social and human rights, and also for children and adolescents in residential care situation